Rancang Bangun Sistem Kendali Smart Home Berbasis Programmable Logic Controller - Hannifannisa Hannifannisa; Hastuti Hastuti (Universitas Negeri Padang, 2020)
Smart Home (Smart Home) can change our lives as if to be smarter because it becomes a symbol where the owner can work automatically. By using a Programmable Logic Controller (PLC) the load at home can be controlled. The PLC used is PLC Outseal Shield V.3. Installed loads consist of: lights and fences. This electronic device controlled by PLC is more efficient in electrical power, cost-effective, convenient, safe, and easy to set up. This PLC uses ladder diagrams as a programming language. This final project uses several other components that are connected to a sensor consisting of an LDR sensor, a PIR sensor, and an infrared sensor. The PIR sensor is capable of detecting up to a range of 6 meters and the infrared sensor is capable of detecting a distance of 3-80 cm with a detection angle <15˚. This final project also uses a dc motor as a driving device to open and close fences